Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Penjumlahan Dan Pengurangan Pecahan Siswa Kelas VII SMP Negeri Pegagan Hilir - Desy, Desy Anzelina Silaen; P.Gultom, Sanggam; M.Panjaitan, Simon (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to determine Student Errors in Solving Addition and Subtraction Fraction Problems for Class VII Students of SMP Negeri 2 Pegagan Hilir in the 2024/2025 Academic Year. This research is a descriptive study with a qualitative approach. The subjects of this study used a purposive sampling technique by taking 3 students of Class VII-1 SMP Negeri 2 Pegagan Hilir who were in accordance with the criteria for selecting research subjects, while data collection techniques were carried out by tests, interviews and documentation. Each test result was analyzed based on the indicator of Student Errors in solving the problem. Based on the results of the study, it can be concluded that students with a high level of error in solving problems (K1) tend to experience errors in understanding the problem, errors in carrying out the calculation process, errors in process skills, and errors in writing answers. Subject K1 can only rewrite the known problem, but to solve the problem Subject K1 cannot solve the problem. Subject K1 made an error in calculating fractions as evidenced by questions number 1, 2, 3, 4, 5 not finding a solution to the problem. Students with a moderate level of error in solving problems (K2) tend to experience process skill errors and errors in writing answers on questions 4 and 5. This can be seen in the indicators of process skill errors and errors in writing answers, subject K2 tends to make mistakes in using formulas or steps that are in accordance with the conditions of the problem. Students with a low level of error in solving problems (K3) tend to experience errors in drawing conclusions on question number 5 part b. This can be seen in the indicator of errors in writing answers, subject K3 makes mistakes in determining the final answer which is aimed at solving the problem incorrectly.